Diagnosis and treatment of stroke: a review of the literature. - Nogueira Jales, Davi; Domingos Lopes De Sousa Neto; Juliano Oliveira de Sousa Santana Silva; Ysa Bruna Araújo Gonçalves; Nara Arcoverde Amorim Barros; Ravennya Muara Oliveira Silveira Moreira; Ananda Vale Nunes; Maria Mariana Helena Paz Teixeira Nunes; Giselle Gomes Santos; Matheus de Pádua Macedo Andrade; Maria Clara Barbosa de Almeida; Thais Vitoria Moura de Carvalho (Brazilian Journal of Implantology and Health Sciences, 2024)
INTRODUCTION: Cerebrovascular accident (CVA) is a serious neurological condition, resulting from changes in cerebral blood flow. It can be ischemic, due to obstruction of blood vessels, or hemorrhagic, caused by the rupture of vessels, with extravasation of blood into the brain. Stroke is one of the leading causes of death and disability in Brazil and worldwide, with an incidence that increases with age. Its symptoms vary according to the brain area affected, including weakness, paralysis, speech and swallowing difficulties, visual changes, and severe headache. Factors such as hypertension, diabetes and high cholesterol are the main risks for the occurrence of stroke. Prevention and proper management of these factors are essential to reduce mortality and sequelae rates. OBJECTIVE: consolidate advances in clinical practices and identify evidence-based guidelines for effective stroke management, contributing to the updating and improvement of clinical practices, public health policies, and education and prevention strategies. METHODOLOGY: This is an integrative literature review, carried out in November 2024, addressing clinical aspects, diagnosis, and treatment. Articles published between 2014 and 2024 were selected, using descriptors such as "stroke", "diagnosis" and "treatment" in the LILACS, MedLine/PubMed and Google Scholar databases. The review included full texts in Portuguese and English and excluded duplicate articles or articles in other languages. RESULT AND DISCUSSION: Advances in the diagnosis and treatment of stroke in the emergency room have been significant, with the improvement of neuroimaging techniques, such as computed tomography and magnetic resonance imaging, allowing for faster and more accurate diagnoses. The introduction of artificial intelligence has enhanced the early detection and triage of patients. In treatment, intravenous thrombolysis and mechanical thrombectomy have shown positive results when applied within therapeutic windows. In addition, the appropriate management of complications, such as intracranial hypertension, and the use of specialized units have contributed to the reduction of mortality and improvement of functional outcomes. However, the implementation of these advances still faces challenges, particularly in areas with limited resources. CONCLUSION: Advances in the diagnosis and treatment of stroke in the emergency room, such as the use of advanced neuroimaging and artificial intelligence, have improved early detection and management. Therapies such as thrombolysis and mechanical thrombectomy, when applied quickly, show good results. However, challenges remain in areas with limited resources. Professional training and infrastructure improvement are essential to maximize the benefits of these innovations.